2009
DOI: 10.1007/s12231-009-9081-8
|View full text |Cite
|
Sign up to set email alerts
|

Illegal Palm Heart (Geonoma edulis) Harvest in Costa Rican National Parks: Patterns of Consumption and Extraction

Abstract: Illegal Palm Heart (Geonoma edulis) Harvest in Costa Rican National Parks: Patterns of Consumption and Extraction. Illegal extraction of non-timber forest products in the tropics is widespread, and many protected areas face the challenge of balancing conservation needs with cultural practices related to the use and extraction of animals and plants. We studied the illegal wild palm heart extraction of Geonoma edulis, locally known as súrtuba, in Volcán Poás and Braulio Carrillo National Parks in Costa Rica. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In this study, there was interest in cultivation of the species close to residents’ homes. The pattern of palm cultivation that occurs when use is suppressed to meet cultural needs was shown in Costa Rica for Geonoma edulis [87]. …”
Section: Discussionmentioning
confidence: 99%
“…In this study, there was interest in cultivation of the species close to residents’ homes. The pattern of palm cultivation that occurs when use is suppressed to meet cultural needs was shown in Costa Rica for Geonoma edulis [87]. …”
Section: Discussionmentioning
confidence: 99%
“…Our knowledge on the trafficking of plants over the Internet had been limited to only a few incidents (e.g. McMahan & Walter 1989;Wolf & Konings 2001;Entwistle et al 2002;Flores-Palacios & Valencia-Diaz 2007;Alacs & Georges 2008;Sylvester & Avalos 2009;Jiménez-Sierra & Eguiarte 2010;Williams et al 2012;Shirey et al 2013) until very recently, when the e-commerce of the endemic plants of Greece was studied in a systematic way (Krigas et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As a comparison, the management strategy for the Brazilian palm Euterpe edulis in the Atlantic forest is to maintain 50-60 seed trees ha -1 [58]. We would like to emphasize that our management recommendations are not based on the matrix model alone, but on the species´ demography Some studies have shown how a culturally driven extraction can become an uncontrolled, nontraditional source of income [60,61]. Since informal stalls selling P. acuminata palm hearts were observed during Holy Week at villages near our study site, quantitative data on P.acuminata local palm heart demand, consumption motivations and preferences should be obtained [60].…”
Section: Implications For Conservationmentioning
confidence: 99%
“…We would like to emphasize that our management recommendations are not based on the matrix model alone, but on the species´ demography Some studies have shown how a culturally driven extraction can become an uncontrolled, nontraditional source of income [60,61]. Since informal stalls selling P. acuminata palm hearts were observed during Holy Week at villages near our study site, quantitative data on P.acuminata local palm heart demand, consumption motivations and preferences should be obtained [60]. Current and past harvest practices [11,62], traditional ecological knowledge and traditional resource management of the species should also be studied in detail [63].…”
Section: Implications For Conservationmentioning
confidence: 99%